A Target Enrichment Bait Set for Studying Relationships among Ostariophysan Fishes - Faircloth, Brant C.; Alda, Fernando; Hoekzema, Kendra; Burns, Michael D.; Oliveira, Claudio [UNESP]; Albert, James S.; Melo, Bruno F. [UNESP]; Ochoa, Luz E. [UNESP]; Roxo, Fabio F. [UNESP]; Chakrabarty, Prosanta; Sidlauskas, Brian L.; Alfaro, Michael E. (Amer Soc Ichthyologists & Herpetologists, 2020)
Target enrichment of conserved nuclear loci has helped reconstruct evolutionary relationships among a wide variety of species. While there are preexisting bait sets to enrich a few hundred loci across all fishes or a thousand loci from acanthomorph fishes, no bait set exists to enrich large numbers (>1,000 loci) of ultraconserved nuclear loci from ostariophysans, the second largest actinopterygian superorder. In this study, we describe how we designed a bait set to enrich 2,708 ultracon served nuclear loci from ostariophysan fishes by combining an existing genome assembly with low coverage sequence data collected from two ostariophysan lineages. We perform a series of enrichment experiments using this bait set across the ostariophysan tree of life, from the deepest splits among the major groups (> 150 Ma) to more recent divergence events that have occurred during the last 50 million years. Our results demonstrate that the bait set we designed is useful for addressing phylogenetic questions from the origin of crown ostariophysans to more recent divergence events, and our in silico results suggest that this bait set may be useful for addressing evolutionary questions in closely related groups of fishes, like Clupeiformes.